2023
DOI: 10.1186/s12967-023-03924-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the pretreatment systemic immune-inflammation index in patients with prostate cancer: a systematic review and meta-analysis

Abstract: Background The systemic immune-inflammation index (SII) is a novel biomarker to predict the prognosis of some malignant tumors based on neutrophil, platelet, and lymphocyte counts. Evidence is scarce about the prognostic value of SII for prostate cancer patients. This systematic review and meta-analysis was conducted to explore the prognostic value of the SII in prostate cancer. Methods The PubMed, Embase, Web of Science, and Cochrane Library (CENT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 72 publications
0
19
1
Order By: Relevance
“…In addition, high SII was also associated with low PFS (HR = 1.80, 95% CI: 1.27-2.56, P = .001). [31] In the present study, SII was observed as a prognostic marker for OS (HR: 2.17, 95% CI: 1.09-4.32, P = .027) but was not predictive for PFS (P = .531). However, PIV was not significantly associated both with survival and progression (P = .069 and .908, respectively).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In addition, high SII was also associated with low PFS (HR = 1.80, 95% CI: 1.27-2.56, P = .001). [31] In the present study, SII was observed as a prognostic marker for OS (HR: 2.17, 95% CI: 1.09-4.32, P = .027) but was not predictive for PFS (P = .531). However, PIV was not significantly associated both with survival and progression (P = .069 and .908, respectively).…”
Section: Discussioncontrasting
confidence: 45%
“…[12,15,30] Based on a meta-analysis of 12 prostate cancer studies, high SII is associated with reduced OS (HR = 1.44, 95% CI: 1.23–1.69, P < .001). [31] In the subgroup analysis, it was found that this relationship did not change according to the cutoff value, ethnicity and tumor type. In addition, high SII was also associated with low PFS (HR = 1.80, 95% CI: 1.27–2.56, P = .001).…”
Section: Discussionmentioning
confidence: 99%
“…58 New research should also extend to other tumor types given that inflammation is a risk factor for progression [59][60][61][62] and survival across prostate, ovarian, breast, and head and neck cancers. 18,[63][64][65][66][67] Our tests for potentially confounding variables revealed that the direct association of SII with survival was not robust when T classification was entered into the model. It is possible that worsening inflammation concomitant with tumor progression may introduce covariance sufficient to cloud the relationships between inflammation, T classification, and survival.…”
Section: Discussionmentioning
confidence: 85%
“…The SII was associated with the prognosis of patients with hepatocellular carcinoma after curative resection in the beginning 29 . In general, SII has been found to have predictive value for the prognosis of various tumors 30–32 . Meanwhile, most studies have shown that a higher SII is associated with the occurrence and poor prognosis of sepsis 21,33 .…”
Section: Discussionmentioning
confidence: 96%